The multi-faceted immune modulatory role of S100A4 in cancer and chronic inflammatory disease - Wong, Thomas; Kang, Reece; Yun, Kyuson (Frontiers in Immunology, 2025)
S100A4 is a Ca2+-binding protein involved in multiple chronic inflammatory and neoplastic conditions. This review focuses on recent advances in the understanding of S100A4 function in immune cells, comparing and contrasting S100A4 regulation of immune responses in cancer and chronic inflammatory diseases. We provide evidence that S100A4 regulation of immune cell function has a profound role in promoting the pathogenesis of cancer and pro-inflammatory conditions. Finally, we discuss relevant future directions to target S100A4 therapeutically in different disease states.